Leverage web analytics for real time website browsing recommendations - Sapateiro, Cláudio (2017)
Trabalho apresentado no 5th World Conference on Information Systems and Technologies (WorldCIST’17), 11-13 de abril 2017, Porto Santo, Madeira Portugal